2021
DOI: 10.3390/app11219971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano Hydrotalcite on the Aging Resistance of a High Binder Content Stone Mastic Asphalt

Abstract: Hydrotalcite, a type of layered double hydroxide (LDH), reveals an interesting potential for the modification of bitumen. The LDH can induce a barrier effect that prevents the loss of volatiles, retards oxidation, and protects against ultraviolet radiation. Such properties can enhance the aging resistance of the bitumen. However, there is a gap in knowledge regarding the effects of the modification with hydrotalcite in the properties of the asphalt mixture. To contribute to fill such a gap, the current study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Layered double hydroxide (LDH) is a layered material with a supramolecular structure [22]. Studies [23,24] have shown that LDHs can heighten the anti-UV aging performance of ABs, which is attributed to their unique structure that provides physical shielding and chemical absorption of UV light [18]. Zhang et al [25] showed that dodecyltrimethoxysilane surface organic modified LDHs (OLDHs) were significantly more compatible with SBS MABs than LDHs, and the OLDH-modified SBS MABs exhibit a superior high-temperature performance and UV aging resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Layered double hydroxide (LDH) is a layered material with a supramolecular structure [22]. Studies [23,24] have shown that LDHs can heighten the anti-UV aging performance of ABs, which is attributed to their unique structure that provides physical shielding and chemical absorption of UV light [18]. Zhang et al [25] showed that dodecyltrimethoxysilane surface organic modified LDHs (OLDHs) were significantly more compatible with SBS MABs than LDHs, and the OLDH-modified SBS MABs exhibit a superior high-temperature performance and UV aging resistance.…”
Section: Introductionmentioning
confidence: 99%
“…They can increase the compatibility of LDHs with ABs and heighten the anti-UV aging performance of OLDH MABs. Furthermore, LDHs can improve the road performance of asphalt mixtures [23]. Zhao et al [27] concluded that adding LDHs can significantly heighten the resistance to water damage and freeze-thaw splitting of UV-aged SBS MA mixtures and thus enhances their high-temperature and long-term low-temperature properties.…”
Section: Introductionmentioning
confidence: 99%